Effect of sprinkler-based water application in mitigating ammonia emissions from beef cattle feedyards - Myeongseong Lee; Brent W. Auvermann; K. Jack Bush; Greg B. Ferguson; Carolina B. Brandani; Kenneth D. Casey; Vinícius N. Gouvêa; Jason K. Smith; Luis O. Tedeschi; Jacek A. Koziel (Biosystems Engineering, 2026)

Diversity and functional group composition drive biogeographic patterns in marine biogenic structural complexity - Dean S. Janiak; Matthew A. Whalen; David R. Branson; Soledad Álvarez; Gail V. Ashton; Nicholas M. Bartkowiak; Simon J. Brandl; João Canning‐Clode; Jordan M. Casey; Max C. N. Castorani; Carolina César‐Ávila; Rachel Collin; et al. (Ecology, 2026)
Biogenic structural complexity is a key driver of biodiversity and ecosystem functioning, yet its ecological and environmental determinants remain poorly understood across broad biogeographic scales. Here, we conducted standardized 90‐day field experiments at 16 coastal sites, spanning a 41‐degree latitudinal gradient, using naturally assembled marine fouling communities on settlement panels. We measured rugosity as our metric of biogenic structural complexity and modeled its relationship with species richness, community composition, community growth rates, and abiotic conditions (salinity and temperature). Species richness increased with temperature and salinity and declined with latitude, with more diverse communities exhibiting greater biogenic complexity due to increased morphological variation. At high‐latitude sites, low‐diversity communities dominated by arborescent bryozoans also had increased complexity. Structural equation models showed that abiotic conditions influenced growth and composition, which in turn shaped complexity. Warmer, saltier sites promoted richness‐driven complexity, while colder conditions favored structurally important dominant taxa. We found that biodiversity is important not only as a beneficiary of complexity but also as a contributor to complexity itself within fouling communities. Our results also demonstrate that both species richness and functional group identity regulate biogenic complexity across environmental gradients, underscoring biodiversity's role in supporting ecosystem structure and resilience in the face of increasing global change. Understanding these relationships is essential for biodiversity conservation and the management of marine ecosystems facing increasing anthropogenic pressures.

Parental perspectives on the use of tumor molecular profiling and germline genetic testing during their children's cancer treatment - Marcelo M. Sleiman; Muriel R. Statman; Mary Rose Yockel; Yelena P. Wu; Jada G. Hamilton; Wendy K. Kohlmann; Jennie Vagher; Soren Feola; Luke D. Maese; Jing Chen; Burton Appel; Casey J. Mehrhoff; et al. (Familial Cancer, 2025)

Simulating the effects of long‐distance dispersal and landscape heterogeneity on the eco‐evolutionary outcomes of range expansion in an invasive riverine fish, Tench ( Tinca tinca ) - Thaïs A. Bernos; Casey Day; Jaclyn Hill; Olivier Morissette; Kenneth M. Jeffries; Nicholas E. Mandrak (Molecular Ecology, 2023)
Predicting how quickly populations expand their range and whether they will retain genetic diversity when they are introduced to new regions or track environmental conditions suited to their survival is an important applied and theoretical challenge. The literature suggests that long‐distance dispersal, landscape heterogeneity and the evolution of dispersal influence populations' expansion rates and genetic diversity. We used individual‐based spatially explicit simulations to examine these relationships for Tench ( Tinca tinca ), an invasive fish expanding its geographical range in eastern North America since the 1990s. Simulated populations varied greatly in expansion rates (1.1–28.6 patches year −1 ) and genetic diversity metrics, including changes in observed heterozygosity (−19 to +0.8%) and effective number of alleles (−0.32 to −0.01). Populations with greater dispersal distances expanded faster than those with smaller dispersal distances but exhibited considerable variation in expansion rate among local populations, implying less predictable expansions. However, they tended to retain genetic diversity as they expanded, suggesting more predictable evolutionary trajectories. In contrast, populations with smaller dispersal distances spread predictably more slowly but exhibited more variability among local populations in genetic diversity losses. Consistent with empirical data, populations spreading in a longer, narrower dispersal corridor lost more neutral genetic variation to the stochastic fixation of alleles. Given the unprecedented pace of anthropogenic environmental change and the increasing need to manage range‐expanding populations, our results have conservation ramifications as they imply that the evolutionary trajectories of populations characterised by shorter dispersal distances spreading in narrower landscapes are more variable and, therefore, less predictable.

Incorporating non-stationarity from climate change into rainfall frequency and intensity-duration-frequency (IDF) curves - Katherine E. Schlef; Kenneth E. Kunkel; Casey Brown; Yonas Demissie; Dennis P. Lettenmaier; Anna Wagner; Mark S. Wigmosta; Thomas R. Karl; David R. Easterling; Kimberly J. Wang; Baptiste François; Eugene Yan (Journal of Hydrology, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Magnetotactic bacteria: concepts, conundrums, and insights from a novel in situ approach using digital holographic microscopy (DHM) - Casey R. Barr; Manuel Bedrossian; Kenneth J. Lohmann; Kenneth H. Nealson (Journal of Comparative Physiology A, 2022)

Seasonal manganese transport in the hyporheic zone of a snowmelt-dominated river (East River, Colorado, USA) - Savannah R. Bryant; Audrey H. Sawyer; Martin A. Briggs; Casey M. Saup; Amelia R. Nelson; Michael J. Wilkins; John N. Christensen; Kenneth H. Williams (Hydrogeology Journal, 2020)

Research Priorities for Achieving Healthy Marine Ecosystems and Human Communities in a Changing Climate - Whitney R. Friedman; Benjamin S. Halpern; Elizabeth McLeod; Michael W. Beck; Carlos M. Duarte; Carrie V. Kappel; Arielle Levine; Robert D. Sluka; Steven Adler; Casey C. O’Hara; Eleanor J. Sterling; Sebastian Tapia-Lewin; et al. (Frontiers in Marine Science, 2020)

Observational Needs of Sea Surface Temperature - Anne G. O’Carroll; Edward M. Armstrong; Helen M. Beggs; Marouan Bouali; Kenneth S. Casey; Gary K. Corlett; Prasanjit Dash; Craig J. Donlon; Chelle L. Gentemann; Jacob L. Høyer; Alexander Ignatov; Kamila Kabobah; et al. (Frontiers in Marine Science, 2019)

Ocean FAIR Data Services - Toste Tanhua; Sylvie Pouliquen; Jessica Hausman; Kevin O’Brien; Pip Bricher; Taco de Bruin; Justin J. H. Buck; Eugene F. Burger; Thierry Carval; Kenneth S. Casey; Steve Diggs; Alessandra Giorgetti; et al. (Frontiers in Marine Science, 2019)

Data Interoperability Between Elements of the Global Ocean Observing System - Derrick Snowden; Vardis M. Tsontos; Nils Olav Handegard; Marcos Zarate; Kevin O’ Brien; Kenneth S. Casey; Neville Smith; Helge Sagen; Kathleen Bailey; Mirtha N. Lewis; Sean C. Arms (Frontiers in Marine Science, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Ocean Data Product Integration Through Innovation-The Next Level of Data Interoperability - Justin J. H. Buck; Scott J. Bainbridge; Eugene F. Burger; Alexandra C. Kraberg; Matthew Casari; Kenneth S. Casey; Louise Darroch; Joaquin Del Rio; Katja Metfies; Eric Delory; Philipp F. Fischer; Thomas Gardner; et al. (Frontiers in Marine Science, 2019)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

What we still don't know about invasion genetics - Dan G. Bock; Celine Caseys; Roger D. Cousens; Min A. Hahn; Sylvia M. Heredia; Sariel Hübner; Kathryn G. Turner; Kenneth D. Whitney; Loren H. Rieseberg (Molecular Ecology, 2015)
Publication of The Genetics of Colonizing Species in 1965 launched the field of invasion genetics and highlighted the value of biological invasions as natural ecological and evolutionary experiments. Here, we review the past 50 years of invasion genetics to assess what we have learned and what we still don't know, focusing on the genetic changes associated with invasive lineages and the evolutionary processes driving these changes. We also suggest potential studies to address still‐unanswered questions. We now know, for example, that rapid adaptation of invaders is common and generally not limited by genetic variation. On the other hand, and contrary to prevailing opinion 50 years ago, the balance of evidence indicates that population bottlenecks and genetic drift typically have negative effects on invasion success, despite their potential to increase additive genetic variation and the frequency of peak shifts. Numerous unknowns remain, such as the sources of genetic variation, the role of so‐called expansion load and the relative importance of propagule pressure vs. genetic diversity for successful establishment. While many such unknowns can be resolved by genomic studies, other questions may require manipulative experiments in model organisms. Such studies complement classical reciprocal transplant and field‐based selection experiments, which are needed to link trait variation with components of fitness and population growth rates. We conclude by discussing the potential for studies of invasion genetics to reveal the limits to evolution and to stimulate the development of practical strategies to either minimize or maximize evolutionary responses to environmental change.

Recommendations for a national agenda to substantially reduce cervical cancer - Jennifer S. Smith; Noel T. Brewer; Debbie Saslow; Kenneth Alexander; Mildred R. Chernofsky; Richard Crosby; Libby Derting; Leah Devlin; Charles J. Dunton; Jeffrey Engle; Maria Fernandez; Mona Fouad; et al. (Cancer Causes & Control, 2013)

Effects of protein kinase A inhibitor and activator on rewarding effects of SKF-82958 microinjected into nucleus accumbens shell of ad libitum fed and food-restricted rats - Soledad Cabeza de Vaca; Xing-Xiang Peng; Seth Concors; Casey Farin; Elena Lascu; Kenneth D. Carr (Psychopharmacology, 2012)

Temperature‐driven coral decline: the role of marine protected areas - Elizabeth R. Selig; Kenneth S. Casey; John F. Bruno (Global Change Biology, 2012)
Warming ocean temperatures are considered to be an important cause of the degradation of the world's coral reefs. Marine protected areas ( MPA s) have been proposed as one tool to increase coral reef ecosystem resistance and resilience (i.e. recovery) to the negative effects of climate change, yet few studies have evaluated their efficacy in achieving these goals. We used a high resolution 4 km global temperature anomaly database from 1985–2005 and 8040 live coral cover surveys on protected and unprotected reefs to determine whether or not MPA s have been effective in mitigating temperature‐driven coral loss. Generally, protection in MPA s did not reduce the effect of warm temperature anomalies on coral cover declines. Shortcomings in MPA design, including size and placement, may have contributed to the lack of an MPA effect. Empirical studies suggest that corals that have been previously exposed to moderate levels of thermal stress have greater adaptive capacity and resistance to future thermal stress events. Existing MPA s protect relatively fewer reefs with moderate anomaly frequencies, potentially reducing their effectiveness. However, our results also suggest that the benefits from MPA s may not be great enough to offset the magnitude of losses from acute thermal stress events. Although MPA s are important conservation tools, their limitations in mitigating coral loss from acute thermal stress events suggest that they need to be complemented with policies aimed at reducing the activities responsible for climate change.

Hydroclimate risk to economic growth in sub-Saharan Africa - Casey Brown; Robyn Meeks; Kenneth Hunu; Winston Yu (Climatic Change, 2011)

Warming Seas in the Coral Triangle: Coral Reef Vulnerability and Management Implications - Elizabeth McLeod; Russell Moffitt; Axel Timmermann; Rodney Salm; Laurie Menviel; Michael J. Palmer; Elizabeth R. Selig; Kenneth S. Casey; John F. Bruno (Coastal Management, 2010)

New insights into global patterns of ocean temperature anomalies: implications for coral reef health and management - Elizabeth R. Selig; Kenneth S. Casey; John F. Bruno (Global Ecology and Biogeography, 2010)
Aim Coral reefs are widely considered to be particularly vulnerable to changes in ocean temperatures, yet we understand little about the broad‐scale spatio‐temporal patterns that may cause coral mortality from bleaching and disease. Our study aimed to characterize these ocean temperature patterns at biologically relevant scales. Location Global, with a focus on coral reefs. Methods We created a 4‐km resolution, 21‐year global ocean temperature anomaly (deviations from long‐term means) database to quantify the spatial and temporal characteristics of temperature anomalies related to both coral bleaching and disease. Then we tested how patterns varied in several key metrics of disturbance severity, including anomaly frequency, magnitude, duration and size. Results Our analyses found both global variation in temperature anomalies and fine‐grained spatial variability in the frequency, duration and magnitude of temperature anomalies. However, we discovered that even during major climatic events with strong spatial signatures, like the El Niño–Southern Oscillation, areas that had high numbers of anomalies varied between years. In addition, we found that 48% of bleaching‐related anomalies and 44% of disease‐related anomalies were less than 50 km 2 , much smaller than the resolution of most models used to forecast climate changes. Main conclusions The fine‐scale variability in temperature anomalies has several key implications for understanding spatial patterns in coral bleaching‐ and disease‐related anomalies as well as for designing protected areas to conserve coral reefs in a changing climate. Spatial heterogeneity in temperature anomalies suggests that certain reefs could be targeted for protection because they exhibit differences in thermal stress. However, temporal variability in anomalies could complicate efforts to protect reefs, because high anomalies in one year are not necessarily predictive of future patterns of stress. Together, our results suggest that temperature anomalies related to coral bleaching and disease are likely to be highly heterogeneous and could produce more localized impacts of climate change.

THE GODAE HIGH-RESOLUTION SEA SURFACE TEMPERATURE PILOT PROJECT - Craig Donlon; Kenneth Casey; Ian Robinson; Chelle Gentemann; Richard Reynolds; Ian Barton; Olivier Arino; John Stark; Nick Rayner; Pierre LeBorgne; David Poulter; Jorge Vazquez-Cuervo; et al. (Oceanography, 2009)

The Multi-Sensor Improved Sea Surface Temperature (MISST) Project - Chelle Gentemann; Peter Minnett; Joseph Sienkiewicz; Mark DeMaria; James Cummings; Yi Jin; James Doyle; Lew Gramer; Charlie Barron; Kenneth Casey; Craig Donlon (Oceanography, 2009)